Epidemiology of Acinetobacter baumannii: analysis of hazard factors associated with positivity cases in Guizhou province, China from 2015 to 2023 - Liang, Zhongzhi; Tian, Di; Huang, Yanlan; Dou, Shanjiang; Yang, Anxin; Chen, Zuyi (Frontiers in Public Health, 2025)
IntroductionThe widely prevalent Acinetobacter baumannii is a gram-negative opportunistic pathogen, with the enormous potential to trigger multiple concurrent diseases. Due to its multidrug resistance, A. baumannii has emerged as a key monitored pathogen of WHO for surveillance in healthcare settings, particularly in intensive care units (ICUs).MethodsTo identify factors associated with A. baumannii infection in Guizhou province, China from 2015 to 2023, a retrospective cross-sectional analysis was carried out with the data from hospital records, electronic medical databases. Fisher’s exact test (gender) and Chi-square were used for statistical tests, while p-values was used to define the statistically significance of variables.Results and discussionOut of 460,620 patients; there were 6,944 positive infection events, with ICU-related infections accounting for 45.77%. Males had a significantly higher risk of A. baumannii infection compared to females, and host factors such as gender and increasing age were associated with greater susceptibility. In addition, infection rates were higher during warmer summer months, suggesting a possible seasonal trend in transmission. Within the population undergoing antibiotic therapy, only polymyxin B demonstrated an alarmingly high level of resistance, whereas other clinically employed antibiotics were invalid. In summary, the statistical data from these years emphasizes that gender and age are main drivers of A. baumannii outbreaks in Guizhou, and follow-up public health interventions need to target these factors to enhance infection control and reduce the spread. Also, the observation of high levels of resistance to multiple antibiotics is a matter of concern, as it presents significant challenges in terms of treatment.